Hubungan Pola Makan Dengan Kadar Kolesterol Pada Polisi Yang Mengalami Gizi Lebih Di Polresta Sidenreng Rappang - Elma Ampangalo; Nurhaedar Jafar; Rahayu Indriasari; Abdul Salam; Aminuddin Syam (Departement of Nutrition, Faculty of Public Health, Hasanuddin University, Makassar, 2021)
Introduction: People who are at risk of having high cholesterol levels are those who adopt adiet that contains saturated fat levels and consumes less fiber. Purpose: This study aims todetermine the relationship between diet and cholesterol levels in overnourished policeofficers.Material and Methods: This research was conducted on 50 police officers at PolrestaSidenreng Rappang. Diet in the police was measured by the SQ-FFQ questionnaire. WhereSQ-FFQ is a method to find out the picture of individual nutritional intake habits at a certaintime. Cholesterol levels were obtained through measurements using Easy Touch GCU anddata for TB (Height), BB (Weight) were obtained from secondary data.. Result: There are 56.0% police officers who have hypercholesterolemia. The results ofstatistical tests using the Fisher Exact test stated that there was a relationship between fiberintake (0.023), frequency of meat (0.029) and frequency of vegetables (0.012) with cholesterol